Effects of hydrogen induced delay fracture on high-strength steel plate of automobile and the improvement - Fengzhu Liu; Yu Zhao (Fracture and Structural Integrity)
Delay fracture is an environmental embrittlement occurring when materials, environment and stress interact with each other and also a form of hydrogen induced material deterioration. It is a leading factor inhibiting the further improvement of strength of steel and iron material. Hence this study analyzed the improved low-carbon Mn-B type ultra-high strength steel plate (1500 MPa) which were processed by conventional heat treatment and heating forming technique and explored the effects of tempering temperature and heating forming technique on the performance of hydrogen induced delay fracture, which provides a reference for the actual application of such kind of steel plate.